An updated review of gastrointestinal toxicity induced by PD-1 inhibitors: from mechanisms to management - Cheng, Yiyu; Ling, Fangmei; Li, Junrong; Chen, Yidong; Xu, Mingyang; Li, Shuang; Zhu, Liangru (Frontiers in Immunology, 2023)
PD-1 inhibitors, as one of commonly used immune checkpoint inhibitors, enable T cells activation and prevent immune escape by blocking the PD-1/PD-L1 signaling pathway. They have transformed the treatment landscape for cancer in recent years, due to the advantages of significantly prolonging patients' survival and improving their life quality. However, the ensuing unpredictable immune-related adverse effects (irAEs) plague clinicians, such as colitis and even potentially fatal events like intestinal perforation and obstruction. Therefore, understanding the clinical manifestations and grading criteria, underlying mechanisms, available diverse therapies, accessible biomarkers and basis for risk stratification is of great importance for the management. Current evidence suggests that irAEs may be a marker of clinical benefit to immunotherapy in patients, so whether to discontinue PD-1 inhibitors after the onset of irAEs and re-challenge after remission of irAEs requires further evaluation of potential risk-reward ratios as well as more data from large-scale prospective studies to fully validate. At the end, the rare gastrointestinal toxicity events caused by PD-1 inhibitors are also sorted out. This review provides a summary of available data on the gastrointestinal toxicity profile caused by PD-1 inhibitors, with the aim of raising clinicians' awareness in daily practice, so that patients can safely benefit from therapy.